(untitled) (Eurasian Journal of Ecology, 2022)
Medicinal plants have been widely used in folk medicine since ancient times. Today, medicinal plants have become an important component of healthcare and pharmaceuticals. Due to a large number of species of plants with medicinal properties, in some countries, there is a wide development of traditional medicine. The flora of Kazakhstan is also rich in species of medicinal plants that have scientific and practical value depending on its climatic and geographical features. One of them, Common toadflax (Linaria vulgaris Mill), a plant belonging to the genus Toadflax, is used in folk medicine and as a raw material for synthetic drugs in the pharmaceutical industry. However, no full research has been conducted in Kazakhstan on the medicinal plant Linaria vulgaris Mill. Therefore, the analysis of phytochemical features of the medicinal plant Linaria vulgaris Mill grown in the conditions of agrobiostation in the Almaty region was carried out. As a result of this study, it was determined that the chemical composition of Linaria vulgaris Mill contains biologically active extractives: amino acids, flavonoids, tannins, and carbohydrates. These data complement the botanical characteristics of this plant and are important for its introduction and expansion of raw materials, and its comprehensive use in medicine, as well as in the pharmaceutical industry. Key words: Linaria vulgaris Mill, Common Toadflax, extract, medicinal plant.